Human capacity challenges in the implementation of a Monitoring and Evaluation system - Maphunye, Mompheleng Ernest (My University, 2014)
A Monitoring and Evaluation (M&E) system is important in a country or public sector organisation as it can assist in the understanding of a country or organisation’s M&E efforts. Information acquired from using the M&E system will then lead to a clearer understanding of the current M&E initiatives, the overall environment where the system is used and some of the institutional arrangements involved. Using the system can also be looked at from a viewpoint of improving the current M&E initiatives and using M&E information obtained from using the system to assist and benefit the intended stakeholders. Based on the above remarks around M&E systems, this study explored the challenges faced by the Gauteng Department of Local Government and Traditional Affairs (DLGTA), in implementing a municipal M&E system. In a probe of the challenges related to the implementation of this system, the study found that department’s lack to properly capacitate the municipal service delivery M&E unit with the required and skilled personnel mostly impacted the department’s efforts to implement a municipal M&E system. The study also found that the challenges of not implementing a municipal M&E system was as a result of the DLGTA as an organisation not properly viewing itself as the coordinating body of municipal M&E in the Gauteng province. By not recognising itself as the coordinating body of M&E in the province, the DLGTA’s efforts were minimal in terms of capacitating its service delivery M&E unit with the right number of personnel, but also highly skilled personnel who have a solid M&E background, training and who could ensure the implementation of a municipal M&E system. A major consequence of the above departmental shortcomings is that they lead to the human capacity challenges of the service delivery M&E unit of the DLGTA that contributed to the non-implementation of a municipal M&E system. This is the system that should be used to conduct municipal M&E and also assist Gauteng municipalities with their M&E functions as mandated by legislation.
Keywords: Monitoring and Evaluation system; Department of Local Government and TraditionalAffairs; Service delivery